2011
DOI: 10.1007/s10865-011-9354-4
|View full text |Cite
|
Sign up to set email alerts
|

The impact of family behaviors and communication patterns on chronic illness outcomes: a systematic review

Abstract: In general, social support from family members affects chronic illness outcomes, but evidence on which specific family behaviors are most important to adult patient outcomes has not been summarized. We systematically reviewed studies examining the effect of specific family member behaviors and communication patterns on adult chronic illness self-management and clinical outcomes. Thirty studies meeting inclusion criteria were identified, representing 22 participant cohorts, and including adults with arthritis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
183
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 227 publications
(198 citation statements)
references
References 82 publications
5
183
0
4
Order By: Relevance
“…18,19 Informal caregivers play a crucial role in supporting diabetes self-management 20,21 and may increase engagement in mhealth interventions. Some IVR-based programs in the United States allow patients to participate with an informal caregiver (''CarePartner'') who receives automated feedback based on the patient's IVR assessments.…”
Section: Barriers To Intervention Engagement and Scalingmentioning
confidence: 99%
“…18,19 Informal caregivers play a crucial role in supporting diabetes self-management 20,21 and may increase engagement in mhealth interventions. Some IVR-based programs in the United States allow patients to participate with an informal caregiver (''CarePartner'') who receives automated feedback based on the patient's IVR assessments.…”
Section: Barriers To Intervention Engagement and Scalingmentioning
confidence: 99%
“…This is in accordance with earlier research on the individual level, which showed that unrealistic expectations and lack of support may negatively affect self-care management in the form of diet and physical activity, as well as the maintenance thereof (Moore & Cooper, 2015; Sharman et al, 2015). Families’ involvement and negative expression of support can be obstructive, depending on the relationship quality and conflict resolution abilities (Mayberry & Osborn, 2014; Rosland, Heisler, & Piette, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Or, does the proposed increase in relationship strength as a result of empathic responses from significant others buffer the negative effects on the relationship due to one partner having CMP? Complexity can also arise when this support or empathic response, viewed by couples as an indicator of relationship strength, translates into solicitousness which has a potentially detrimental effect on pain outcomes [8,[28][29][30]. It has also been suggested that by providing help with everyday tasks, significant others are reducing the amount of activities for the person with pain, leaving more time for them to focus/ruminate on their condition.…”
Section: Discussionmentioning
confidence: 99%